Perceptions about Usefulness and Attitudes toward UX work: a survey with software startup Brazilian professionals - Guerino, Guilherme Corredato; Martinelli, Suéllen; Choma, Joelma; Leal, Gislaine Camila Lapasini; Balancieri, Renato; Zaina, Luciana (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2023)
User eXperience (UX) work in the software industry involves employing user-centered practices and techniques to obtain and apply knowledge about the users. In this sense, UX work can help software startups to have a competitive advantage since these companies have a challenging context characterized by small teams and a lack of resources. However, the perspectives of startup professionals on UX work are yet to be explored, despite growing interest in the field. This paper aims to explore the perceptions of startup professionals about the usefulness of the methods and techniques used in UX work and at what moments of user interaction with the product or service they are using. To achieve this goal, we conducted a survey with 90 professionals from software startups in Brazil. For data analysis, we adopted descriptive and inferential statistical methods. We identified that software startup professionals seek to understand user needs, capture feedback, and test with users, these being the most attitudes applied toward UX work. Interviews are the most used method, but usability testing, competitive analysis, and high-fidelity prototyping are also useful for startups in different stages of maturity. Besides, UX data is collected at distinct moments, particularly during user interactions with the product. Our findings allowed us to verify the perceived usefulness of software startup professionals toward UX work, but this view varies according to the startup stage.